Determinants of skilled birth attendants for delivery in Nepal - Baral, Y R; Lyons, K; Skinner, J; van Teijlingen, E R (Kathmandu University Medical Journal, 2012)
This review is to explore the factors affecting the uptake of skilled birth attendants for delivery and the issues associated with women’s role and choices of maternal health care service for delivery in Nepal. Literature was reviewed across the globe and discussed in a Nepalese context. Delivery by Skilled Birth Attendance serves as an indicator of progress towards reducing maternal mortality worldwide, the fifth Millennium Development Goal. Nepal has committed to reducing its maternal mortality by 75% by 2015 through ensuring accessibility to the availability and utilisation of skilled care at every birth. The literature suggests that several socio-economic, cultural and religious factors play a significant role in the use of Skilled Birth Attendance for delivery in Nepal. Availability of transportation and distance to the health facility; poor infrastructure and lack of services; availability and accessibility of the services; cost and convenience; staff shortages and attitudes; gender inequality; status of women in society; women’s involvement in decision making; and women’s autonomy and place of residence are significant contributing factors for uptake of Skilled Birth Attendance for delivery in Nepal. The review found more quantitative research studies exploring the determinants of utilisation of the maternal health services during pregnancy in Nepal than qualitative studies. Findings of quantitative research show that different social demographic, economic, socio-cultural and religious factors are responsible for the utilisation of maternal health services but very few studies discussed how and why these factors are responsible for utilisation of skilled birth attendants in pregnancy. It is suggested that there is need for more qualitative research to explore the women’s role and choice regarding use of skilled birth attendants services and to find out how and why these factors are responsible for utilisation of skilled birth attendants for delivery. Qualitative research will help further exploration of the issues and contribute to improvement of maternal health services. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6223 Kathmandu Univ Med J 2010;8(3):325-32